Translation strategies used in the Spanish dubbing of the songs of the movie Toy Story 2 - Villanelo Ninapaytan, María (2023)
This article has to identify Franzon’s translation strategies used in the Spanish dubbing of the songs from the movie Toy Story 2. This was a descriptive investigation since the different types of Franzon’s strategies and their frequency of use were identified. appearance. On the other hand, this research had a non-experimental design since only the behavior of said study phenomenon was observed without manipulating the translation strategies variable. Finally, the logical inductive method was used in the analysis of the samples. The most frequently used translation strategies were completely rewriting the lyrics of the song with 35% and adapting the translation to the original music with 30%. One conclusion that can be drawn would be that Franzon’s translation strategies used in the Spanish dubbing of the songs from the movie Toy Story 2 were to completely rewrite the lyrics of the song, adapt the translation to the original music, translate the lyrics without taking into account the music and translate the lyrics and adapt the music